A new approach for indirect capture measurements: The DICER neutron transmission station at LANSCE - Stamatopoulos, Athanasios; Koehler, Paul; Couture, Aaron; DiGiovine, Brad; Rusev, Gencho; Ullmann, John (HNPS Advances in Nuclear Physics, 2022)
Direct (n,γ) measurements on radioactive nuclei can often be challenging. Substantial effort has been devoted to developing indirect techniques and perform measurements on short-lived radionuclides of astrophysical interest. A new indirect technique is being explored at the Los Alamos Neutron Science Center (LANSCE) which enables the calculation of average neuron capture properties from neutron transmission data. A station for neutron transmission, has been under commissioning during the last two years at LANSCE. The Device for Indirect Capture Experiments on Radionuclides (DICER) is currently capable of carrying out measurements on stable cylindrical samples with a diameter as small as 1 mm and mass as low as a few mg. The first year of operation indicate that the DICER instrument is ready to perform its first measurement on a radioactive sample (88Zr, t1/2=83.4 days) which is planned for the winter of 2021. A brief description of the apparatus and details on the latest DICER results will be presented.